GDH3 encodes a glutamate dehydrogenase isozyme, a previously unrecognized route for glutamate biosynthesis in Saccharomyces cerevisiae. - Avendaño, A (1997)
It has been considered that the yeast Saccharomyces cerevisiae, like many other microorganisms, synthesizes glutamate through the action of NADP+-glutamate dehydrogenase (NADP+-GDH), encoded by GDH1, or through the combined action of glutamine synthetase and glutamate synthase (GOGAT), encoded by GLN1 and GLT1, respectively. A double mutant of S. cerevisiae lacking NADP+-GDH and GOGAT activities was constructed. This strain was able to grow on ammonium as the sole nitrogen source and thus to synthesize glutamate through an alternative pathway. A computer search for similarities between the GDH1 nucleotide sequence and the complete yeast genome was carried out. In addition to identifying its cognate sequence at chromosome XIV, the search found that GDH1 showed high identity with a previously recognized open reading frame (GDH3) of chromosome I. Triple mutants impaired in GDH1, GLT1, and GDH3 were obtained. These were strict glutamate auxotrophs. Our results indicate that GDH3 plays a significant physiological role, providing glutamate when GDH1 and GLT1 are impaired. This is the first example of a microorganism possessing three pathways for glutamate biosynthesis.